2018
DOI: 10.1039/c8nj02756k
|View full text |Cite
|
Sign up to set email alerts
|

NaOH-promoted reaction of 1,1-dihaloalkenes and 1H-azoles: synthesis of dihetaryl substituted alkenes

Abstract: We have developed a useful and simple process for the NaOH-promoted reaction of 1,1-dihaloalkenes and 1H-azoles to afford dipyrazolyl alkenes under mild and transition-metal-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Interestingly, an alternative route to these α-ketoamide products from N -alkynyl azoles was reported by Hwang in 2017 [76]. This method employs copper catalyst and irradiation with blue LEDs in the presence of 1 atm of O 2 (Scheme 43).…”
Section: Reactions Of N-alkynyl Azolesmentioning
confidence: 99%
“…Interestingly, an alternative route to these α-ketoamide products from N -alkynyl azoles was reported by Hwang in 2017 [76]. This method employs copper catalyst and irradiation with blue LEDs in the presence of 1 atm of O 2 (Scheme 43).…”
Section: Reactions Of N-alkynyl Azolesmentioning
confidence: 99%
“…It is still desirable to develop mild but effective methods, which allow the construction of the C–X bond with high functional group tolerance. The Ullmann reaction is a traditional method using aryl halides and nucleophiles under transition metal catalysis [ 9 , 10 ]. Nevertheless, owing to its harsh reaction conditions, it is not applicable in certain cases.…”
Section: Introductionmentioning
confidence: 99%
“…Robert et al., reported the nitrogen atom of indoles can be functionalized with ynamides through base catalysis [Scheme 1 equation v] [22] . Cui and their research gruop reported that N ‐alkynyl pyrazoles reacted with pyrazoles in the presence of base to give mixture of alpha and beta substituted dipyrazolyl derivatives [Scheme 1 equation vi] [23] . Exploration of ynamide reactivity is emerging, [24] and different methods were established to obtain various heterocyclic and application oriented molecules [25] .…”
Section: Introductionmentioning
confidence: 99%
“…[22] Cui and their research gruop reported that N-alkynyl pyrazoles reacted with pyrazoles in the presence of base to give mixture of alpha and beta substituted dipyrazolyl derivatives [Scheme 1 equation vi]. [23] Exploration of ynamide reactivity is emerging, [24] and different methods were established to obtain various heterocyclic and application oriented molecules. [25] However, less attention has been paid on selectively tuning the reactivity of ynamides.…”
Section: Introductionmentioning
confidence: 99%